2019
DOI: 10.1590/1676-0611-bn-2018-0549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on the bathymetric distribution of the flecked box crab Hepatus pudibundus (Herbst, 1785) (Crustacea: Aethroidea) in the Southeastern Brazilian coast

Abstract: This study evaluated the relationships between environmental factors and the spatio-temporal distribution of H. pudibundus, with the hypothesis of differential occupation in coastal areas of southeastern Brazil. The samplings took place monthly in January-December 2000 period, along nine transects from 2 to 40 m of depth, in Ubatuba region, northern coast of São Paulo. We collected 1808 individuals of H. pudibundus. The highest abundance was recorded in winter in the transects 10-25 m deep. Abundance was posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…According to the CA, the distribution of males and females was similar in both periods and were associated with spring and summer. This pattern is common for H. pudibundus and has already been recorded in Ubatuba by and Bernardes et al (2019), and in other regions on the Brazilian coast, for example, in Cananéia (São Paulo) by Miazaki (2017), in Balneário Camboriú (Santa Catarina) by Sardá et al (2013). The spring and beginning of summer are the periods that most favor the occurrence of several decapod crustacean species in Ubatuba due to the entrance of the SACW to 20 m deep (Fransozo et al, 2016;Pires-Vanin, 1993).…”
Section: Likewise Juveniles Of Other Brachyurans Such As the Swimming Crabssupporting
confidence: 63%
See 1 more Smart Citation
“…According to the CA, the distribution of males and females was similar in both periods and were associated with spring and summer. This pattern is common for H. pudibundus and has already been recorded in Ubatuba by and Bernardes et al (2019), and in other regions on the Brazilian coast, for example, in Cananéia (São Paulo) by Miazaki (2017), in Balneário Camboriú (Santa Catarina) by Sardá et al (2013). The spring and beginning of summer are the periods that most favor the occurrence of several decapod crustacean species in Ubatuba due to the entrance of the SACW to 20 m deep (Fransozo et al, 2016;Pires-Vanin, 1993).…”
Section: Likewise Juveniles Of Other Brachyurans Such As the Swimming Crabssupporting
confidence: 63%
“…(2014) and Bernardes et al. (2019), and in other regions on the Brazilian coast, for example, in Cananéia (São Paulo) by Miazaki (2017), in Balneário Camboriú (Santa Catarina) by Sardá et al. (2013).…”
Section: Discussionmentioning
confidence: 94%
“…The SACW intensifies the Cabo Frio upwelling (Stech & Lorenzzetti, 1992) since its physical and chemical features increase nutrient production that favors primary production (Castro-Filho et al, 1987 Coefficients greater than or equal to +0.4, or lower than or equal to −0.4 were considered ecologically relevant (Rakocinski et al, 1996) and are presented in the plot. BT, bottom temperature; OM, organic matter percentage; H', diversity; J', evenness; S', richness above 21°C (Bernardes et al, 2019;Petti et al, 1996;Pires-Vanin & Matsuura, 1993). Therefore, environmental conditions caused by the upwelling more intensely affect species that are adapted to temperatures close to 20°C or lower, such as A. spinicarpus (De Léo & Pires-Vanin, 2006), decreasing the diversity index during the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that low temperatures modulate the occurrence of Brachyura species during spring and summer in Macaé, and on the coast of the state of São Paulo (Bernardes et al, 2019;Costa et al, 2016;Sousa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation